(untitled) (Philological Studies, 2019)
Through an analysis of the novel Flisar’s novel Potovanje predaleč and Blatnik’s novel Tao ljubezni in this paper are represented textual and travel practices in contemporary Slovene travelogue novel. This analysis includes the postmodern modes of representation and deals with representational regimes as a problematic object of knowledge with uncertain ontological status and epistemological values.